The cumulative social adversity hypothesis of psychosis: Intolerance of uncertainty and aberrant salience mediate the association between humiliation and psychotic-like experiences - Bielawski, Tomasz; Misiak, Błażej (Frontiers in Psychiatry, 2025)
BackgroundThe social defeat hypothesis, here framed as cumulative social adversity (CSA) to avoid disempowering terminology, posits that individuals with long-term experience of an unwanted, subordinate position present an elevated risk of psychosis. It has been observed that humiliation might be the most central component of the CSA hypothesis that increases the risk of psychosis through specific information processing patterns. The present study aimed to further investigate as to whether two cognitive processing patterns, i.e., aberrant salience (AS) and intolerance of uncertainty (IU), play a mediating role in the association between CSA and psychotic-like experiences (PLEs).MethodsA total of 1308 non-clinical young adults (aged 31.1 ± 5.9 years, 47.9% men) were assessed with self-reports recording the occurrence of PLEs, AS, IU, and cumulative humiliation via computer-assisted web interview over a 6-month period. A theory-driven, serial mediation model was analyzed.ResultsHumiliation was not directly associated with the level of follow-up PLEs. However, two mediation paths linking humiliation and PLEs were statistically significant after adjustment for age, gender, education, monthly income, and baseline depressive symptoms. The first one led through AS (without a mediating effect of IU) and the second one led through IU and AS (a serial mediation). The indirect association of humiliation with PLEs through a mediating effect of IU (i.e., without AS) was not statistically significant.ConclusionsOur findings suggest that cognitive processing patterns, such as AS, and to a lesser extent IU, may serve as important psychological mechanisms through which cumulative humiliation may lead to the occurrence of PLEs.